ANALISIS PENGARUH RASIO LIKUIDITAS TERHADAP FINANCIAL DISTERSS PADA PERUSAHAAN INFRASTRUKTUR YANG TERDAFTARDI BURSA EFEK INDONESIA PERIODE 2018 – 2022 - India Bahagia (Adisam Publisher, 2025)
This research uses independent variables, namely Current Ratio and Quick Ratio with the dependent variable, namely Financial Distress. The object of research is infrastructure companies listed on the Indonesia Stock Exchange for the 2018–2022 period. Sample selection was carried out using a purposive sampling technique and a sample of 8 companies was obtained. The aim of this research is: Testing and analyzing the eflect of the Quick Ratio on profit growth in Infrastructure companies listed on the Indonesia Stock Exchange for the period 2018 - 2022. Testing and analyzing the eflect of the Quick Ratio on profit growth in Infrastructure companies listed on the Indonesia Stock Exchange for the period 2018 - 2022.After conducting research using multiple linear analysis methods, it can be concluded: 1. Current Ratio has no eflect on profit growth in banking companies for the 2018-2022 period. 2. The Quick Ratio has no eflect on profit growth in banking companies for the 2018-2022 period